Necessity Analysis of Access Layer OTN Construction - Zerong Deng; Yanbin Liu; Quanxin Hou (Dianxin kexue)
The service characteristics of the local transmission network access layer were firstly analyzed. The services of the access layer would be diversified and had higher bandwidth for carrying the services of the LTE backhaul, the OLT uplinks, and the private lines for big customers, the smart city services and so on. Then the features of the access layer OTN technology were briefly described, which were the large-bandwidth transparent transmission capability, multi-service access capability, reliable protection and good operation-and-maintenance. Taking construction of the access layer OTN system in a central area of a certain south city for example, the multi-services carried by it were analyzed. At last, the necessity of constructing the access layer OTN system was detailed illustrated by the capacity challenges for the access layer of local transport network, the infrastructural constraints of constructing pipes and optical cables, the advantages and disadvantages of constructing the access layer OTN system. It suggests that building the access layer OTN system is an ideal choice for bearing the multi-services for the local transport network access layer.